Harvesting sorghum stover - Fairbanks, G.E.; Hoover, J.D. (Kansas State University. Agricultural Experiment Station, 2011)
Two types of big round balers and a small stackmaker were used to harvest grain sorghum stubble after the grain was harvested during the fall and winter months of 1975. The stubble was about 21 inches high and about 4 inches of stubble was left after windrowing.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Sorghum stover; Round baler